(untitled) (Archives of Pediatrics of Uruguay, 2020)
The global development of vaccines has enabled us to control some infectious diseases and has become a powerful public health tool. Despite this, vaccines have some neurological side effects, such as the so-called Hypotonic-Hyporesponsive Episode (HHE), an adverse event following vaccination and immunization (AEFI). Even though it is rare, it is considered to be a severe adverse effect. The objective of this article is to report about a HHE case and to review the literature on the subject. The case is of a 2-month-old infant who, after 3 hours of receiving the first dose of the combined pentavalent vaccine, developed a hypotonic episode with cyanosis of seconds of duration. HHE usually happens hours after the vaccine is administered and it shows a sudden onset of generalized hypotonia, hyporesponsiveness, pale skin or cyanosis. A diagnosis of exclusion was made, since the symptoms looked serious on the infant. Most episodes have been linked to cellular or acellular pertussis. It is essential to carry out AEFI surveillance in order to develop effective and safe vaccination schedules for the entire population.